iSketchVis: Data Exploration through Sketch-based Charting - Browne, Jeffrey; Lee, Bongshin; Henry Riche, Nathalie; Carpendale, Sheelagh; Sherwood, Timothy (In Proceedings of EuroVis 2011, Poster Compendium, June 2011, 2011)
Basic information visualization tasks are now common operations in work places – often through the use of simple charts in spreadsheets, created on individual workstations. While these simple visualizations are incredibly useful, especially in a collaborative environment, the status quo is far more decidedly low-tech. Collaborators often share visualizations in a meeting by manually drawing them on a whiteboard. Sharing control is as easy as passing a pen, revising charts involves merely erasing and redrawing, and new charts come into existence simply by someone drawing what they want to see. However, populating handdrawn charts with data can be tedious, and people frequently resort to indicating approximate trends for discussion purposes.